Hidden Transfers of Assets and Hidden Payouts of Profit - Kobal, Aleš (Institute for Local Self-Government and Public Procurement Maribor, 2016)
The concept of "hidden payout of profit" is characteristic for tax law, but inappropriate for corporate law, although it became deep-rooted in this field by practice. Within the context of corporate law it is not only about the problem of profit payouts, but also about the protection of the so-called tied up assets of a capital company within the so-called principle of capital preservation. The purpose of the corporate legislation is to prevent inadmissible interferences of shareholders or associates in the company's assets. Unlike corporate law, the purpose of tax law is to protect (fiscal) interests of the state, primarily to protect the tax base of the company as an independent and only subject to taxation, therefore the payouts of profit don't have an effect on the amount of the tax base, irrespective of whether the company pays out the profit in an open or hidden way. Hidden payouts of profit - as the open ones - do not reduce the tax base for income. The subject of the discussion are both aspects - the corporate aspect of hidden transfers of assets and the tax aspects of hidden transfers of assets within the law of joint-stock companies and limited liability companies.